2022
DOI: 10.3390/molecules27154902
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and Prebiotic Activities (Lactobacillus spp.) of Gelatine-Based Gels Formulated with Agave Fructans and Agave Syrups as Sucrose and Glucose Substitutes

Abstract: This research developed model foods of gelatine-based gels, where carbohydrates from Agave tequilana Weber var. Azul (agave syrups or/and agave fructans) were incorporated into gel formulations as healthy sucrose and glucose substitutes. The sugars (sucrose and glucose) were substituted by agave carbohydrates (agave syrups and agave fructans), obtaining the subsequent gel formulations: 100% agave syrup (F2 gel), 100% agave fructan (F3 gel), and 50% agave syrup–50% agave fructan (F4 gel). The unsubstituted gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Although there was high water activity at the midpoint of the treatments, an increase in agavins had a significant effect on cohesiveness, while elasticity was mainly affected by agave syrup. These functional ingredients altered and improved the textural properties of the gelatin gummies, in line with what other authors have reported [29,31], in which the ingredients form a more uniform network because due to the nature of the branched structure of the fructooligosaccharides and DP of the agavins, they form stronger internal bonds capable of supporting secondary deformations [40] despite having high Aw. The predicted values and observed values of TPA and Aw are shown in Table 1.…”
Section: Formulation Of a Gummy With Agavins And Agave Syrupsupporting
confidence: 89%
See 1 more Smart Citation
“…Although there was high water activity at the midpoint of the treatments, an increase in agavins had a significant effect on cohesiveness, while elasticity was mainly affected by agave syrup. These functional ingredients altered and improved the textural properties of the gelatin gummies, in line with what other authors have reported [29,31], in which the ingredients form a more uniform network because due to the nature of the branched structure of the fructooligosaccharides and DP of the agavins, they form stronger internal bonds capable of supporting secondary deformations [40] despite having high Aw. The predicted values and observed values of TPA and Aw are shown in Table 1.…”
Section: Formulation Of a Gummy With Agavins And Agave Syrupsupporting
confidence: 89%
“…Therefore, it can be incorporated into new gelatin gummy formulations [29,30]. The use of agave syrup in combination with agavins or alone has shown a prebiotic effect in gels [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…TLC and PC are simple methods but have low sensitivity and accuracy in detecting monosaccharides. TLC can be used to separate carbohydrates using an organic mobile phase followed by staining; fructose and glucose can easily be distinguished as differently colored spots on the plate [ 55 ]. HPLC has been used extensively to identify constituent monosaccharides and determine their molar ratios.…”
Section: Characterisationmentioning
confidence: 99%
“…In these studies, TPA was the main technique to characterize changes in texture based on different processing methods and gelling agent sources, specifically in gelatin. While there are studies which instrumentally characterize the changes in gel systems when sugar reduction occurs [ 16 , 17 , 18 ], they usually lack a sensory component, and because the correlation between instrumental and sensory data is dependent on the matrix, more research is required to characterize sugar reduction in individual food products, such as gels.…”
Section: Introductionmentioning
confidence: 99%